Reconfigurable Intelligent Surface-Assisted Uplink Sparse Code Multiple Access - Al-Nahhal, Ibrahim; Dobre, Octavia A.; Basar, Ertugrul (IEEE communications letters, 2021)
Reconfigurable intelligent surface-empowered communication (RIS) and sparse code multiple access (SCMA) are promising candidates for future generations of wireless networks. The former enhances the transmission environments, whereas the latter provides a high spectral efficiency transmission. This letter proposes, for the first time, a low-cost design for RIS-assisted uplink SCMA (SCMA-RIS) scheme to improve the conventional SCMA spectrum efficiency. The message passing algorithm (MPA) is utilized and modified to decode the SCMA-RIS transmitted signals. Moreover, a low-complexity decoder for the SCMA-RIS scheme is proposed to significantly reduce the MPA decoding complexity and improve the bit error rate performance of the conventional SCMA. Monte Carlo simulations and complexity analysis are presented, which support the findings.